Optimasi Kinerja Jaringan WLAN Berdasarkan Analisis QoS dan Strategi - Retno, Dwi; Aini, Syarifah; Apriansyah, Apriansyah (TIN: Terapan Informatika Nusantara, 2025)
The Wireless LAN (WLAN) network at the Air Limau Village Office faces operational challenges in the form of connection slowdowns during high loads, dependence on primary devices, and weak security protocols. This study aims to optimize the performance of the WLAN network and improve its security and performance. The method used is a SWOT analysis to map strategic factors and network measurement using the QoS (Quality of Service) method. The QoS test results show that the network performance is mostly in the "very good" to "good" category for the Packet Loss, Delay, and Jitter parameters. However, the test data indicates a significant performance decline at certain times, where the Throughput value drops to 299kbps (lowest) from the morning average (1688kbps), which validates the slowdown during peak hours. Strategically, the SWOT analysis highlights weaknesses in the centralized architecture (tree topology) and external threats. Based on these findings, the proposed solution is to optimize the topology to a hybrid to increase flexibility and redundancy, accompanied by regular maintenance and upgrades to the network infrastructure.